TATA CARA HIDUP ORANG MELAYU RIAU: WARISAN BUDAYA YANG LESTARI - Trirahmayati, Tiara; Yasnel (PT. Jurnal Center Indonesia Publisher, 2025)
The Malay community of Riau is known for its rich culture, which reflects noble values of life passed down through various traditions and ways of life from their ancestors. The principle of